Critically Evaluate How Technology Enhances International Banking Performance - Okonkwo Doris Ngozi; Adeniyi Akinwumi John; Daga Dogara James; Oreoluwa Blessing Omojola (Britain International for Academic Research (BIAR-Publisher), 2026)
This study critically evaluates how technology enhances international banking performance, with a particular focus on Nigerian banks engaged in global transactions. The research examines key technologies adopted in international banking, their impact on operational efficiency, the speed and reliability of cross-border transactions, and the challenges associated with technological adoption. An ex post facto research design was employed, using secondary data from 2000 to 2023 collected from the Central Bank of Nigeria, National Bureau of Statistics, and the World Bank. Data were analyzed using descriptive statistics and Ordinary Least Squares (OLS) regression to establish relationships between technology adoption and banking performance indicators. Findings reveal that technologies such as online banking platforms, mobile banking applications, and SWIFT systems are widely adopted, with emerging technologies like blockchain and artificial intelligence being gradually implemented. Technology adoption significantly improves operational efficiency, reduces transaction time, increases reliability of cross-border transfers, and enhances overall banking performance. However, challenges such as high implementation costs, cybersecurity risks, and inadequate staff training impede optimal technology adoption. The study concludes that technology is a critical driver of competitiveness, efficiency, and profitability in international banking and recommends strategic adoption, capacity building, robust cybersecurity measures, and continuous monitoring to maximize its benefits. These findings contribute to the literature on digital banking and provide practical insights for banking managers and policymakers seeking to leverage technology for improved international banking performance.